Cues that Matter: The Potential for black campaigns in the 2024 general election - Hasse Jubba; Henky Fernando; Yuniar Galuh Larasati; Umar Warfete (UIN Sunan Gunung Djati, 2023)
Black campaigns that occurred in 2014 and 2019 also have the potential to emerge in the 2024 general elections in Indonesia. Not only does black campaigning have the potential to create public distrust of a fair electoral process, but it also has the potential to polarize society. This phenomenon has not been scientifically considered in previous studies. This study focuses on the question,